Plan de promoción y publicidad para "Josenka boutique" del cantón Quevedo, provincia de Los Ríos, año 2015. - Anzules Castañeda, Alexandra Elizabeth (2015)
Promotion and advertising Plan is a specific and essential marketing tool to achieve the objectives Josenka Boutique marketing, through the implementation of efficient advertising and promotional strategies is intended to achieve Capture the attention of the population objective and in turn will maximize sales. According to the diagnosis made at Josenka Boutique, it was found that from the year 2013 sales fell considerably in contrast to previous years, it follows that it is product of the transfer of business to a new and comfortable local, but according to the market analysis determined that it is a consequence of poor implementation of marketing strategies. The results of the market study determined that Josenka Boutique presents a little positioning, several people in the area still do not know the business, others are unaware of where it is located, etc., is projected to be the scarce information spread about business product. The SWOT analysis indicated that the boutique presents a little positioning, holds little advertising and not implementing Attractants promotions that capture the attention of the target audience, facts that Quevedo and this disadvantage have negatively influenced the participation of business in the market of the canton has been take advantage of competition to win more customers. To develop this study and structure the plan of promotion and advertising, has resorted to methods, techniques and research instruments for the purpose of collecting the information necessary to achieve the objectives and at the same time verify the hypothesis. Field study carried out in the Josenka boutique Quevedo canton, to effect surveyed 372 inhabitants (demand) and 10 owners of boutiques in the sector, likewise interviewed the owner of the business, to obtain information regarding the current situation of the business.